1992
DOI: 10.1002/1097-0142(19920401)69:7<1645::aid-cncr2820690702>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Signet ring cell carcinoma of the stomach

Abstract: Between 1965 and 1985, 51 of 1500 patients (3.4%) with gastric cancer who had gastric resection had signet ring cell gastric cancer. Patients with this form of cancer tended to be younger and female; the tumors were smaller and involved the stomach body, serosal invasion was less prominent, and lymph node metastases were less likely to be present. Early mucosal and submucosal cancer was present in 54.9% of the patients with the signet ring cell and in 24.6% with other types of gastric cancer. In 15.7% of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
1
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 14 publications
5
86
1
3
Order By: Relevance
“…The prevalence of GSRC among patients with gastric cancer has been reported to range from 3.4 to 39% [1][2][3], and, in South Korea, incidences of 12.2 and 8.7% have been reported [4,5]. One group of researchers reported that GSRC shows a slightly higher predominance among females and younger individuals [1], whereas others have found no gender difference [3,[5][6][7]. From the prognostic point of view, several authors have demonstrated that GSRC does not have a poorer prognosis than the other types of stomach cancer [1,2,5,7], but the issue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of GSRC among patients with gastric cancer has been reported to range from 3.4 to 39% [1][2][3], and, in South Korea, incidences of 12.2 and 8.7% have been reported [4,5]. One group of researchers reported that GSRC shows a slightly higher predominance among females and younger individuals [1], whereas others have found no gender difference [3,[5][6][7]. From the prognostic point of view, several authors have demonstrated that GSRC does not have a poorer prognosis than the other types of stomach cancer [1,2,5,7], but the issue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…One group of researchers reported that GSRC shows a slightly higher predominance among females and younger individuals [1], whereas others have found no gender difference [3,[5][6][7]. From the prognostic point of view, several authors have demonstrated that GSRC does not have a poorer prognosis than the other types of stomach cancer [1,2,5,7], but the issue remains controversial. Others have suggested that, among advanced gastric cancers, GSRC has a poorer prognosis [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…1 The prognosis after surgery for early gastric carcinoma generally is favorable, with the 5-year survival rate at present exceeding 90% in Japan. 2 However, there are cases of recurrence: The rate in cases of early gastric carcinoma is 2.2%. 3 We reported previously that the growth pattern based on a volumetric analysis is an important prognostic factor in early gastric carcinoma.…”
mentioning
confidence: 98%
“…The great majority of mutations in the p53 gene are missense in type, leading to production of full-length proteins with an altered conformation and abnormal biological properties (Hollstein et al, 1991). Unlike the wild-type protein, which has a short halflife, the great majority of tetramers containing mutant protein are stable and therefore readily detectable by immunochemistry using antibodies reactive to p53 (KikuchiYanoshita et al, 1992 Cancer, 1981Cancer, , 1993Maehara et al, 1992 (Kakeji et al, 1993 (Table II).…”
mentioning
confidence: 99%